(untitled) (City: History, Culture, Society, 2021)
The problem of money counterfeiting is quite multifaceted, starting from the idea, motive, searching of raw materials and resources, continuing with the manufacture of the counterfeit money, ending with the sale of the finished products. The sale of counterfeit money usually took place in large trading cities and trade fairs. This article presents and analyzes the evidence about the detection of counterfeit money in Berdychiv city, which are preserved in historical archives, newspaper publications and among the predecessors’ publications. After analyzing a number of the materials of the criminal cases of the state historical archives and newspaper publications, numerous testimonies were obtained characterizing the city of Berdychiv as one of the potent centres of counterfeit money sale, starting from the first quarter of the XIX century and continuing for another hundred years. The first mention of the sale of counterfeit banknotes in Berdychiv relates to the well-known counterfeiter Ignacy Ceizik, who launched large-scale criminal activities in various regions of the Russian Empire, continuing the illegal production of money even after detention and imprisonment. Coins minted on behalf of the Russian government for the Kingdom of Poland at the Warsaw Mint have had a strong position in Kyiv and Volyn provinces’ money market. The prevalence and popularity of these coins led to the appearance of the counterfeits, the mass discovery of attempts to sell which in the cities of Berdychiv and Brody prompted the authorities of the Austrian Empire to prohibit the exchange of Russian money in the banks. As a great trade centre, the city of Berdychiv has also become an attractive destination for counterfeit money imported from London throughout most of the XIX century. The sale of the counterfeits was carried out by the participants in the Polish Uprising of 1831 through an established network of influential Jewish bankers. In the second half of the XIX century, the city of Berdychiv attracted not only the sellers of the counterfeit money but also their producers. Detained in 1860 in the Skvyra district of Kyiv province, the sender of fake 25-ruble credit notes during the interrogation pointed out that they were made in a sheltered workshop in Berdychiv. The possibility of importing of counterfeit money into the city for sale in the early XX century, but in addition to counterfeit credit notes, the police officers also discovered the counterfeit postage stamps, according to the publications of the newspapers in Berdychiv.